Monitoring Fuel Oil Tank Level at Petrol Station - Radzi, Nur Syahirah (Universiti Teknologi PETRONAS, 2017)
Fuel oil measuring in underground tank is indispensable since the early development of petrol station and until today the manual method is still praticing. The manual method is by inserting a calibrated stick in order to get the height of the oil in the tank. Then after obtaining the height, the volume of oil can be calculated or can be obtain by referring to a tabulated chart of the respective tank design. The method is still being practice by the current petrol station but with an improvement of ready installed measuring stick in the tank with imprinted volume on the stick. The measurement are conducted every day. In the latest measuring technology,it integrates a digitize equipment which is by using magnetostrictive. To obtain the fuel oil height and volume, the operator have to activate the device in order to get the recent measurement of the fuel oil. Thus, this method will not be monitor in real time as it only operate when it is activated on turned on.